Studi Penerapan Layanan Bimbingan Kelompok terhadap Konsep Diri Peserta didik Generasi Z - Anjar, Tri; Agus Wibowo; Mudaim (Counseling Milenial (CM), 2025)
This study stems from the issue of adolescents living in the era of social media, where various information flows in without strict filtering. The research aims to examine the effect of group guidance services on the self-concept of Generation Z students at State of high school 5 in Metro city. The research problem is formulated as follows: Does the implementation of group guidance services affect the self-concept of Generation Z students. The study employed an experimental research method with a one-group pretest–posttest design. The research sample consisted of 10 students categorized as Generation Z at State of high school 5 in Metro city. Data were collected using a self-concept scale comprising 30 items. The data were analyzed using a different test technique. The results showed a significant difference in the self-concept of Generation Z students before and after receiving group guidance services. Based on these findings, it is concluded that the implementation of group guidance has an effect on the self-concept of Generation Z students at State of high school 5 in Metro city